Factors associated with providing social security benefits for traumatic brain injury resulting from occupational accidents - Denismar Borges de Miranda; Rita Franco Rego; Denise Nunes Viola; Verônica Maria Cadena Lima; Edriene Barros Teixeira (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
INTRODUCTION: The Occupational Accident (OA) is considered to be an important public health problem in Brazil. Traumatic Brain Injury (TBI) is the most common among them. The TBI is associated with high morbidity and mortality rates among workers. OBJECTIVE: To identify factors associated with providing social security benefits for TBI due to occupational accidents according to the specific type of economic activity in Brazil, in 2009. METHODS: This is a cross-sectional study that was conducted with all workers who were part of the General Regime of Social Security (RGPS) of Brazil. Secondary data were obtained from the National Information System Benefit, from the Synchronized National Register of the Ministry of Finance and from the General Register of Employed and Unemployed Persons. Data were analyzed using the multiple logistic regression method. RESULTS: We analyzed 2,006 cases of social security benefits for traumatic brain injury due to Occupational Accident. Factors associated with the concession of the benefit according to the economic activity of the Company of the beneficiary were identified. Associations were found with sex, income and the region of the Company. CONCLUSION: Factors associated with the concession of social security benefits by TBI resulting from OA differ depending on the type of economic activity in the study. Understanding these factors may contribute to the planning of preventive policies.